2008
DOI: 10.1097/cmr.0b013e328307bf3f
|View full text |Cite
|
Sign up to set email alerts
|

Molecular staging by multimarker reverse transcriptase-polymerase chain reaction assay of lymphatic drainage and blood from melanoma patients after lymph node dissection

Abstract: Reverse transcriptase-polymerase chain reaction (RT-PCR)-mediated detection of melanoma cells may be a prognostic factor for disease outcome. We investigated the presence of melanoma cells in lymphatic drainage and blood in melanoma patients after lymph node dissection (LND) via the highly sensitive multimarker (MM) RT-PCR assay. We collected 24-h lymph fluid (LY) and peripheral blood (BL) from 107 stage III melanoma patients after radical LND (59 axillary and 48 ilioinguinal LND). Tyrosinase, MART1 and uMAGE … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
13
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 24 publications
1
13
0
Order By: Relevance
“…Indeed, several studies have shown that multiple-marker analysis allows for the detection of circulating melanoma cells in a higher percentage of melanoma patients than single-marker analysis [9][10][11][24][25][26][27][28]30,36]. Among the markers analyzed in these studies, some have shown high specificity for melanoma cells (MART-1, TRP-1, TRP-2, MAGE-3, paired box homeotic gene transcription factor 3, b1-4-N-acetylgalactosaminyltransferase), whereas others were found to be positive also in healthy volunteer samples (p97, MUC18, gp100) [9][10][11][24][25][26][27]30,36]. Our study has confirmed the advantage of multi-marker analysis for the detection of circulating melanoma cells that had been shown in earlier studies.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Indeed, several studies have shown that multiple-marker analysis allows for the detection of circulating melanoma cells in a higher percentage of melanoma patients than single-marker analysis [9][10][11][24][25][26][27][28]30,36]. Among the markers analyzed in these studies, some have shown high specificity for melanoma cells (MART-1, TRP-1, TRP-2, MAGE-3, paired box homeotic gene transcription factor 3, b1-4-N-acetylgalactosaminyltransferase), whereas others were found to be positive also in healthy volunteer samples (p97, MUC18, gp100) [9][10][11][24][25][26][27]30,36]. Our study has confirmed the advantage of multi-marker analysis for the detection of circulating melanoma cells that had been shown in earlier studies.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have shown that the presence of circulating melanoma cells detected by RT-PCR is associated with shorter overall and progression-free survival [9][10][11][12][13][14][15][16][17][18][19][20][21][28][29][30][31][32]. But other studies did not confirm the prognostic value of RT-PCR detection of circulating melanoma cells [22,23,[33][34][35][36]. metastases and negative values of investigated markers.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…The samples were centrifuged again, and the pellets were collected. Total cellular RNA was prepared from fresh or frozen pellets as described previously 12. RNA was further purified from trace amounts of DNA according to the method recommended by the DNase I (RNase-free) producer (Gibco-BRL), except that one-fourth of the recommended amount of DNase I was used.…”
Section: Methodsmentioning
confidence: 99%
“…We have demonstrated previously with using two-marker or multimarker reverse transcriptase-polymerase chain reaction (MM RT-PCR) technique in the group of cutaneous melanomas with regional node metastases (microscopic and macroscopic), that positive result of this assay correlated significantly with early melanoma recurrence and shorter survival 10–12…”
mentioning
confidence: 99%